Clonal colony in the Early Devonian cnidarian Sphenothallus from Brazil - Van Iten, Heyo; Leme, Juliana De Moraes; Simões, Marcello Guimarães [UNESP]; Cournoyer, Mario (Inst Paleobiologii Pan, 2019)
The fossil record of polypoid cnidarians includes a number of taxa that were incorrectly identified as either tubiculous worms or plants. The holotype of the putative alga Euzebiola clarkei (Ponta Grossa Formation, Lower Devonian, Brazil), originally described under the name Serpulites sica, is re-described and re-figured as a species of Sphenothallus, a medusozoan cnidarian. Unlike Sphenothallus from other localities, the black, organic-walled Ponta Grossa specimen consists of a single parent tube that is confluent with the apical ends of at least 18 daughter tubes. The pattern of arrangement of the daughter tubes, which are arrayed in single file along the exposed face and the two thickened margins of the parent tube, partly resembles the whorl-like pattern of arrangement of colonial polyps of certain scyphozoan cnidarians. For these reasons, the Ponta Grossa Formation material figures prominently in the argument that Sphenothallus was a medusozoan cnidarian capable (in at least one species) of clonal budding.
Keywords: Cnidaria; Medusozoa; Scyphozoa; Hydrozoa; clonal budding; Devonian; Brazil